Film thickness and friction behaviour of thermally aged lubricating greases - Gonçalves, David (2016)
Non-additized batches of lubricating greases were subjected to an artiﬁcial thermal aging procedure. The fresh and aged samples were then tribologically characterized through ﬁlm thickness measurements and Stribeck curves, over a large range of entrainment speeds on a ball-on-disc test rig at different operating temperatures, ensuring fully ﬂooded conditions. The results were analysed at the light of the physical and chemical changes regarding the fresh greases. The ﬁlm thickness increased for all greases after the thermal aging. The ﬁlm thickness plateau at low speeds also changed and for certain greases it disappeared under the same range of entrainment speeds. The friction behaviour also changed considerably given the changes to the lubrication regimes for the same speeds.